2007
DOI: 10.1016/s1607-551x(09)70402-4
|View full text |Cite
|
Sign up to set email alerts
|

PON1 Activity is Inversely Related to LDL ApoB Carbonyl Content in Patients with Coronary Artery Disease

Abstract: The objective of this study was to investigate apolipoprotein B (apoB) carbonyl content as a parameter for studying low-density lipoprotein (LDL) oxidation in coronary artery disease (CAD) risk assessment and to explore the relationship between apoB carbonyl content (an index of protein oxidation) and paraoxonase 1 (PON1) activity in CAD patients and controls. A total of 200 patients suffering from CAD and 150 normal individuals were included in the present study. CAD patients were classified into two groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…[14] However, it has also been suggested that the quality of the PON1 enzyme may be a better predictor of CHD risk than the PON1 genotype; because as compared to controls, patients consistently demonstrate lower PON1 activity and concentration levels, regardless of their PON1 genotype. [38][39][40][41] The PON1-55 polymorphism is not extensively studied among Indian populations, and the present study results are consistent with those of the previous study by Sanghera et al, [25] suggesting that PON1-55 has no independent effect on CAD. However, the LL and *L allele are signiÞ cantly associated with CAD among nonsmokers, which should be considered further with a large-population study.…”
Section: Discussionsupporting
confidence: 92%
“…[14] However, it has also been suggested that the quality of the PON1 enzyme may be a better predictor of CHD risk than the PON1 genotype; because as compared to controls, patients consistently demonstrate lower PON1 activity and concentration levels, regardless of their PON1 genotype. [38][39][40][41] The PON1-55 polymorphism is not extensively studied among Indian populations, and the present study results are consistent with those of the previous study by Sanghera et al, [25] suggesting that PON1-55 has no independent effect on CAD. However, the LL and *L allele are signiÞ cantly associated with CAD among nonsmokers, which should be considered further with a large-population study.…”
Section: Discussionsupporting
confidence: 92%
“…S1; Supplementary Data are available online at www.liebertonline .com/dna). Finally, a total of 47 eligible association studies were identified (Ayub et al, 1999;Hasselwander et al, 1999;Karakaya et al, 1999;Itahara et al, 2000;James et al, 2000;Liu et al, 2000;Sentí et al, 2001;Bai et al, 2002;Ferré et al, 2002;Luo et al, 2002Luo et al, , 2008Rahmani et al, 2002;Suehiro et al, 2002;Azarsiz et al, 2003;Mackness et al, 2003Mackness et al, , 2006Qian et al, 2003;Wang et al, 2003;Lacinski et al, 2004;Gö çmen et al, 2004Gö çmen et al, , 2008Li et al, 2004;Rodríguez-Esparragó n et al, 2005;Su et al, 2005Su et al, , 2006Blatter Garin et al, 2006;Chi et al, 2006;Kerkeni et al, 2006;Kotur-Stevuljevic et al, 2006;Qi et al, 2006;Sarkar et al, 2006;Sharma et al, 2007;Singh et al, 2007;Yang et al, 2007;Bhattacharyya et al, 2008;Gamboa et al, 2008;Lu et al, 2008;Sentü rk et al, 2008;Troughton et al, 2008;…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Changes in HDL subfractions observed in various diseases under oxidative stress conditions can be a cause of reduction of PON-1 activity [11,21,36]. In fact, low levels of serum PON-1 have been reportedly associated with obesity-related disorders and CVD [1,4,22,34,36]. Interestingly, many studies have shown significantly lower levels of PON-1 (measured by phenylacetate and/or paraoxon as substrate in all studies) in ESRD patients with and without HD treatment compared to controls [6, 7, 10, 12-14, 16-18, 24, 26, 27, 31, 32, 35].…”
Section: Paraoxonase-1 In Esrdmentioning
confidence: 99%